Identification of a nonsense mutation in the granulocyte-colony-stimulating factor receptor in severe congenital neutropenia. - Dong, F (1994)
Severe congenital neutropenia (Kostmann syndrome) is characterized by profound absolute neutropenia and a maturation arrest of marrow progenitor cells at the promyelocyte-myelocyte stage. Marrow cells from such patients frequently display a reduced responsiveness to granulocyte-colony-stimulating factor (G-CSF). G-CSF binds to and activates a specific receptor which transduces signals critical for the proliferation and maturation of granulocytic progenitor cells. Here we report the identification of a somatic point mutation in one allele of the G-CSF receptor gene in a patient with severe congenital neutropenia. The mutation results in a cytoplasmic truncation of the receptor. When expressed in murine myeloid cells, the mutant receptor transduced a strong growth signal but, in contrast to the wild-type G-CSF receptor, was defective in maturation induction. The mutant receptor chain may act in a dominant negative manner to block granulocytic maturation.